Analisis Jabatan dalam Mewujudkan Efektivitas Kerja pada PT. Nur Aen Agritama - Muhammad Naufal Ridho; Enjang Suherman; Flora Patricia Angela (Universitas Batanghari, 2023)
PT. Nur Aen Agritama is a company engaged in the processing of paddy into rice in Karawang Regency. The purpose of this research is to provide a clear explanation of job analysis so that they can carry out tasks that are in accordance with education, skills and expertise so that the quality of human resources within the company/organization can continue to improve. The method used in this study is descriptive qualitative with data collection using interview techniques on the main informant, namely the director of PT. Nur Aen Agritama, key informant for production manager, marketing HRD, also finance, and supporting informants and documentation. Data analysis used descriptive analysis. The results of this study are the exposure of job analysis at PT. Nur Aen Agritama consisting of 1 top manager position, 6 middle managers positions, and 7 first-level managers. Each position has a working relationship with other positions so that production runs smoothly. Almost all positions are dominated by high school graduates/equivalent. But work effectiveness as not materialized at PT. Nur Aen Agritama due to a lack of understanding regarding job analysis resaulting in a double job